Monitoring bird diversity in Western Ghats of Kerala - J. Praveen and P. O. Nameer (CURRENT SCIENCE, VOL. 96, NO. 10, 25 MAY 2009, 2009)
This communication elaborates a case study in Kerala, where 61 surveys have been conducted from 1990 to 2008 in 21 protected areas and reserve forests in the southern Western Ghats for monitoring bird fauna using the amateur bird-watcher network. Four different methodologies have been used in these surveys, with encounter-based transects being the most common. A significant result of these surveys is in identifying the relative conservation value of these forest areas in protecting endemic and threatened avifauna